Parental Nutritional Knowledge and Its Association with Child Growth and Development: Evidence from Bengkalis District, Indonesia - Aulia, Vanny; Qosyasih, Nelis Nazziatus Sadiah; Garzia, Meyke (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Nutrition plays a crucial role in supporting children’s overall growth, development, and bodily functions. A balanced nutritional intake provides the energy and essential nutrients necessary to sustain life and promote children’s physical, social, emotional, and cognitive advancement. This study aims to explore the relationship between parents’ nutritional knowledge and child growth and development in Bengkalis Regency, Indonesia. Employing an associative quantitative approach, data were collected through questionnaires and documentation. The sample consisted of 100 parents of children aged 5–6 years, selected using simple random sampling. Data analysis included descriptive statistics (univariate and bivariate analyses), with variable relationships tested using the Chi-Square method. The findings revealed that most parents had moderate nutritional knowledge (54%), while 23% had low knowledge and 23% had high knowledge. Regarding children’s nutritional status, 53% were categorized as usual, 25% as undernourished, and 22% as severely malnourished. Further analysis indicated that children of parents with low nutritional knowledge had a higher risk of poor nutrition and developmental delays. Conversely, children of parents with moderate nutritional knowledge tended to have better nutritional status, with 77.7% classified as having usual nutritional status. These findings reinforce that parental nutrition literacy significantly influences children’s nutritional outcomes and developmental progress. However, the study has limitations, including a small sample size, reliance on self reported data, and a cross sectional design that restricts causal interpretation. Future research should adopt longitudinal or mixed methods approaches to capture changes more accurately. The study recommends strengthening community based nutrition education, integrating routine growth and development screening, and enhancing cross sector collaboration to improve access to nutritious foods for families.